Inter-Regional Cooperation (KAD) based institution in the tourism sector in Madura - Eni Sri Rahayuningsih (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This study aims to analyze the Inter-Regional Cooperation (KAD) institution in the tourism sector in Madura to support Presidential Regulation Number 80 of 2019 concerning the DEWI CEMARA program (Tourism Village with Smart, Independent, and Prosperous Communities). This qualitative research has used the triangulation method for data collection. This study shows great potentials have supported tourism development in Madura; yet, they have complex problems. This problem has led to the establishment of the KAD in the tourism sector in Madura, whose aim is to exploit the regional potential and overcome tourism problems collectively using mutual benefit principles. From 2017 to the present, these objectives have not been achieved due to the following reasons: (1) KAD has not been supported by the commitment of regional heads who are willing to facilitate cross-sector and cross-regional cooperation and resources; (2) KAD has not been supported by cross-sectoral and cross-regional planning documents; (3) no good cooperation occurs among the government, the private sector and the community; and (4) moral hazard such as egoistic/opportunistic, free riders, and tragedy of common are still obviously seen